Improving the technology of feed distribution on dairy farms for cattle - E. A. Nikitin; V. V. Kirsanov; G. N. Samarin; V. Yu. Sidorova; R. A. Mamedova; I. V. Knyazeva; A. V. Titenkov (Аграрная наука Евро-Северо-Востока, 2024)
The article provides an analysis of existing feeding technologies on dairy farms, which are divided into four types and evaluated by the accuracy of dosing concentrated and bulky feeds into a mixer. In the first type of feeding, the feed  is prepared by a trailer mixer-distributor, where each component is dosed by a loader, the accuracy of the feed dosage was measured by the onboard weighing system "Dailly TMR Manager". The second type involves the use of a self-propelled feed dispenser mixer with self-loading. The third feeding scheme in a stationary feed mill provides for the use of a stationary mixer-distributor of feed and automated distribution means (a wheeled robot or a feed wagon). The fourth type of feeding technology is presented in the form of a self-propelled chassis, on which the feed mixer capacity and an autonomous dosing system of concentrated feeds for different age and gender technological groups are installed. The high dosage error of concentrated feeds was shown by the first feeding technology, the maximum recorded value of 17 % out of 100 measurements. When dosing bulky feeds, the first and fourth feeding technologies showed a high error of up to 6 %. The technology of feeding in a stationary feed mill has a high accuracy of dosing of all types of feed, but the main disadvantages of this technology are high metal consumption, energy consumption and bulkiness of the structure, which increases the cost of equipment and its maintenance. The specific gravity of concentrates in the feeding diet requires the use of high-precision dosing equipment, eliminating dosage errors associated with the human factor. An overdose of concentrated grains increases the cost of milk, increases the risk of acidosis, and a lack reduces the efficiency of animal nutrient metabolism. Based on the above analysis of existing technologies, a feeding technology is proposed using a self-propelled mixer distributor with an automatic weight control system and a self-loading device for bulky feeds, and for concentrated feeds – a robotic device equipped with an accurate dispenser of concentrated feeds and mineral additives with a maximum error of 2 %.